Behavioural switching during oscillations of intracellular Ca2+ concentration in free-swimming human sperm. Issue 1 (March 2021) - Torrezan-Nitao, Elis; Guidobaldi, Héctor; Giojalas, Laura; Barratt, Christopher; Publicover, Stephen
Lay summary: A human sperm must swim to the egg to fertilise it. To do this the sperm uses different types of swimming (behaviours) as they are needed. When we watch sperm swimming we see that they regularly change behaviour, sometimes repeatedly switching between two different types. Calcium ions inside cells are crucial in controlling many cell functions and in sperm they play a key role in regulating their behaviour. Here we have measured the concentration of calcium ions inside swimming human sperm. We found that in 12/35 (34%) of the cells we assessed, the concentration of calcium changed repeatedly, averaging more than one cycle of rise and fall per minute. These changes in the concentration of calcium ions occurred as the sperm switched swimming stroke, suggesting that oscillation of calcium concentration is involved in controlling the switching of sperm behaviour. Impaired sperm motility is an important cause of subfertility in men. Understanding how sperm behaviour is controlled will allow the development of treatments that can rescue the fertility of sperm with impaired motility.